Universal Health Coverage for Inclusive and Sustainable Development : Country Summary Report for Peru - Vermeersch, Christel (World Bank Group, Washington, DC, 2014)
Peru is an upper middle-income country that has experienced fast economic growth (average of 6.9 percent per year from 2004 to 2013, according World Developing Indicators, WDI) combined with a reduction in poverty and inequality over the past decade. Economic growth was led by exports and domestic demand, generating an increase in private investment, attracting foreign capital, and strengthening public finances. The population living in poverty and extreme poverty fell from 58.7 percent and 16.4 percent in 2004 to 25.8 percent and 6 percent in 2012, respectively (INEI 2014a). Inequality has also decreased, with the Gini index declining from 0.503 in 2004 to 0.48.1 in 2010 (WDI).